2019
DOI: 10.1104/pp.18.00934
|View full text |Cite
|
Sign up to set email alerts
|

ABC Transporter-Mediated Transport of Glutathione Conjugates Enhances Seed Yield and Quality in Chickpea

Abstract: The identification of functionally relevant molecular tags is vital for genomics-assisted crop improvement and enhancement of seed yield, quality, and productivity in chickpea (Cicer arietinum). The simultaneous improvement of yield/productivity as well as quality traits often requires pyramiding of multiple genes, which remains a major hurdle given various associated epistatic and pleotropic effects. Unfortunately, no single gene that can improve yield/productivity along with quality and other desirable agrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 74 publications
(136 reference statements)
1
15
0
Order By: Relevance
“…Geographic location, altitude, the extent of heat stress, and the composition and number of genotypes might account for this difference. In agreement with this study, wide phenotypic variations were detected for GY and yield‐related traits among 291 chickpea accessions (Basu et al., 2019). Various authors have observed phenotypic, genotypic, and genotype × environment interactions for traits studied in chickpea genotypes (Krishnamurthy et al., 2011; Paul et al., 2018; Saeed & Darvishzadeh, 2017; Upadhyaya et al., 2011).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Geographic location, altitude, the extent of heat stress, and the composition and number of genotypes might account for this difference. In agreement with this study, wide phenotypic variations were detected for GY and yield‐related traits among 291 chickpea accessions (Basu et al., 2019). Various authors have observed phenotypic, genotypic, and genotype × environment interactions for traits studied in chickpea genotypes (Krishnamurthy et al., 2011; Paul et al., 2018; Saeed & Darvishzadeh, 2017; Upadhyaya et al., 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Genome‐wide association studies have the potential to identify causal genetic intervals but require large and properly structured study populations, detailed and accurate phenotyping, and significant resources for genomic analysis. Alternatively, one can understand the degree of genetic variation in tested materials so that suitable parents can be selected to develop biparental populations for trait–locus mapping and molecular breeding (Basu et al., 2019; Kujur et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Five SNPs had two potential candidate genes each, for instance, SNP at Gm08_15803242 ( qHSW-8-8 ) had Glyma08g20770 and Glyma08g20780 at 38.65 and 27.86 kb downstream. These two genes code for ATP binding cassette (ABC) transporter protein with biological function of transport; transmembrane transport which have been demonstrated to play significant role in regulating seed size/weight with effect on seed yield [ 51 ]. These two genes together with Glyma06g17520, Glyma06g44510, Glyma09g04840, Glyma11g27070, Glyma12g33280, Glyma13g18280 and Glyma13g17890 are annotated to be involved in sugar/sucrose/ monosaccharide transport.…”
Section: Resultsmentioning
confidence: 99%
“…MADS-box genes have been reported to be jack of all traits [ 84 ]. The network also covered the two genes from multidrug resistance-associated protein 6; ABC transporter transmembrane region; ABC transporter proteins which have recently demonstrated to enhance seed yield and quality in chickpea [ 51 ]. The functional co-expression network capturing some key genes which had some orthologs demonstrated to regulate seed development, implies that integration of co-expression can be one of the strategies to identify keys underlying major agronomic traits in crops.…”
Section: Discussionmentioning
confidence: 99%
“…ABC transporters are essential for plant growth and development and play an important role in processes such as germination, organ formation and organ growth. They are involved in germination by interfering with various cellular processes (Kanai et al 2010;Basu et al 2019). For example, they can be negatively involved in the germination process by transferring abscisic acid (Ko et al 2014).…”
Section: Associated Genes With Ndgmentioning
confidence: 99%